2012
DOI: 10.3390/ijms13044655
|View full text |Cite
|
Sign up to set email alerts
|

Injurious Effects of Curcumin on Maturation of Mouse Oocytes, Fertilization and Fetal Development via Apoptosis

Abstract: Curcumin, a common dietary pigment and spice, is a hydrophobic polyphenol derived from the rhizome of the herb Curcuma longa. Previously, we reported a cytotoxic effect of curcumin on mouse embryonic stem cells and blastocysts and its association with defects in subsequent development. In the present study, we further investigated the effects of curcumin on oocyte maturation and subsequent pre- and post-implantation development, both in vitro and in vivo. Notably, curcumin induced a significant reduction in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…This effect resulted in a reduced ability of oocytes to be fertilized, increased blastocyst apoptosis, and reduced blastocyst implantation ratio and development. These results were confirmed in oocytes collected from female mice after feeding them with curcumin supplementation (40 μM) for four days [ 67 ]. Another in vitro study highlighted that the degree of damage induced by curcumin (6, 12, or 24 μM curcumin for 24 h) on mouse blastocyst at the implantation stage and during the early post-implantation stage is dose-dependent.…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 64%
“…This effect resulted in a reduced ability of oocytes to be fertilized, increased blastocyst apoptosis, and reduced blastocyst implantation ratio and development. These results were confirmed in oocytes collected from female mice after feeding them with curcumin supplementation (40 μM) for four days [ 67 ]. Another in vitro study highlighted that the degree of damage induced by curcumin (6, 12, or 24 μM curcumin for 24 h) on mouse blastocyst at the implantation stage and during the early post-implantation stage is dose-dependent.…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 64%
“…In vivo studies of oocytes that were fertilized and transferred to the uterus at the blastocyst stage indicated that in female ICR mice with reasonable diet and water containing 10 to 40 μM of curcumin, blastocysts implantation rate was decreased. In addition, the blastocysts development after implantation and the life time of them were lower than groups that did not receive curcumin (Chen & Chan, ).…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin, via ROS generation, triggers apoptosis in the inner cell mass (ICM) cells of mouse blastocysts leading to impairment of embryo development . A more recent study confirms the harmful effects of curcumin; specifically, both in vitro and in vivo curcumin treatment lead to significant reduction in the rate of oocyte maturation, fertilization, and embryonic development . On the contrary, a previous study has shown that short‐term (1 H) pretreatment with curcumin effectively prevents MG‐induced apoptosis in mouse embryonic stem cells and blastocysts, and this might be attributed to the antioxidant properties of the polyphenol .…”
Section: Dietary Polyphenolsmentioning
confidence: 97%
“…Catechins Positively influence ovarian function and lifespan [297] Resveratrol Extends the productive life of ovary [298] Genistein Exposure for the first 5 days of life negatively influences reproductive structures [299], with changes in oviduct morphology and reduced fertility [300]; long-term neonatal exposure ameliorates lipid patterns in obese PCOS [301] Daizein Exposure for the first 5 days of life negatively influences reproductive structures [299], whereas promotes bone development and attenuates deterioration of bone tissue during aging [302] Silymarin Coadministration with gonadotropins results in granulosa cell apoptosis decrease in ART, with no effect in promoting follicular development [246] Aloe vera Long-term exposure restores ovarian steroid status, glucose sensitivity [304], and reverts dyslipidemic status [305] in PCOS Embryo EGCG Acts against oxidative stress in fetal organs and tissues [306]; treatment of rat embryos ameliorates hyperglycemia-induced embryonic vasculopathy and malformations [307] Resveratrol Suppresses harmful effect of MG in embryo development by reducing ROS generation and apoptosis in blastocysts, both in vitro and in vivo [308]; improves glucose homeostasis and lipid metabolism in diabetic dams and prevents oxidative stress in whole embryos [309] ECG In vitro exposure increases apoptosis in mouse blastocysts, desorption of post-implantation embryos and decreases fetal weight [310] Puerarin 24 H treatment induces apoptosis in mouse blastocysts and decreased embryonic viability, both in vitro and in vivo [311] Curcumin 24 H exposure decreases implantation rate and increases desorption of post-implantation mouse embryos [312]; reduces oocyte maturation, fertilization and embryo development both in vitro and in vivo [313]; short-term (1h) exposure prevents MG-induced apoptosis in mouse embryonic stem cells and blastocysts [314] PRF May interfere with fetal ductus arterious dynamics [315]; reduced maternal intake during third trimester completely reverts ductal constriction [317] Genistein Neonatal female mouse treatment limits ability to support preimplantation embryo [318] Pregnancy Resveratrol Does not change placental pathology parameters in a PE rat model [319]; inhibits VEGFR-1 release in human PE placental tissue and trophoblasts, and increases the expression of the protective enzyme...…”
Section: Polyphenols Oocytementioning
confidence: 99%